2020
DOI: 10.1002/ece3.6264
|View full text |Cite
|
Sign up to set email alerts
|

Drought conditions alter litter decomposition and nutrient release of litter types in an agroforestry system of China

Abstract: Evaluating how decomposition rates and litter nutrient release of different litter types respond to changes in water conditions is crucial for understanding global carbon and nutrient cycling. However, it is unclear how decreasing water affects litter mixture interactions for the maize–poplar system in arid regions. Here, the responses of the litter decomposition process and litter mixture interactions in the agroforestry system to changes in water conditions (control, light drought, and moderate drought) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Drought can affect litter decomposition in multiple ways (Allison et al 2013;Santonja et al 2015). For instance, drought can decrease litter decomposition via decreasing litter quality (Sanaullah et al 2012;Xie et al 2020), reducing quantity, diversity and activities of decomposers (Kheir et al 2019;da Silva et al 2020) and altering soil physio-chemical properties (Duarte et al 2017). We found that drought directly decreased litter decomposition (Fig.…”
Section: Effects Of Drought On Litter Decompositionmentioning
confidence: 74%
See 1 more Smart Citation
“…Drought can affect litter decomposition in multiple ways (Allison et al 2013;Santonja et al 2015). For instance, drought can decrease litter decomposition via decreasing litter quality (Sanaullah et al 2012;Xie et al 2020), reducing quantity, diversity and activities of decomposers (Kheir et al 2019;da Silva et al 2020) and altering soil physio-chemical properties (Duarte et al 2017). We found that drought directly decreased litter decomposition (Fig.…”
Section: Effects Of Drought On Litter Decompositionmentioning
confidence: 74%
“…Climate change is projected to result in more intensive drought in some regions in the world (Peltier and Ogle 2019;da Silva et al 2020). Drought can not only affect litter traits such as litter N concentration (Sanaullah et al 2012;Xie et al 2020), but also influence soil physio-chemical properties (e.g. soil moisture, temperature and pH) and diversity, quantity and activities of decomposers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing effects of climate change (e.g., warming, drought, extreme heat, heavy rainfall) on ecosystem processes (Runting et al 2017;Pires et al 2018), patterns of N dynamics described here will be destabilized (Nielsen and Ball 2015;Homyak et al 2017). For instance, changes in the quality of litter inputs caused by droughts will arguably affect N inputs via decomposition processes (Prieto et al 2019;Xie et al 2020). The effects of soil moisture limitations caused by droughts will constrain N mineralization processes (Homyak et al 2017;Schimel 2018) and affect N 2 O emissions (Li et al 2020;Barrat et al 2020).…”
Section: Uncertainties and Suggested Further Studiesmentioning
confidence: 98%